The Effects of the Use of Module-based Concordance Materials and Data-driven Learning (DDL) Approach in Enhancing the Knowledge of Collocations of Prepositions among Malaysian Undergraduate Law Students - Yunus, Kamariah (2012)
Computer technology has revolutionised English Language Teaching and Learning (ELLT) with the advent of Corpus Linguistics. The application of Corpus Linguistics in classrooms, in the so called Corpus (Data)-Driven Learning (DDL) approach, makes use of ‘real-life’ concordance data, and the concordance tools train learners to perform hands-on concordancing. It also trains learners to derive at linguistic rules and meanings based on observations of repetitive words or collocation patterns as the KWIC (Key-Word-in-Contexts) in the concordance lines. While many have criticised the application of independent (‘hard’) DDL, as it lacks teacher supervision and increases learners’ cognitive load, this paper aims at investigating the effectiveness of the use of both paper-based (scaffolded) concordance materials (‘soft’) DDL and (‘hard’) DDL (independent online searching) in enhancing the knowledge of collocations of prepositions among law undergraduates at UniSZA (University of Sultan Zainal Abidin), Malaysia. 40 law undergraduates were involved in this 10-week experimental study, where 20 students were placed in the experimental group and treated with module-based DDL, and the other 20 were put in the comparison group and treated with the conventional approach. The findings showed that the students in the DDL group performed significantly better than the students in the comparison group in the sentence-completion and in determining the semantic function tasks. This study recommends explicit teaching of collocations of prepositions via ‘soft’ and ‘hard’ DDL instructions as opposed to independent or ‘hard’ DDL.